The complete chloroplast genome sequence of Camellia chuongtsoensis. Issue 1 (2nd January 2021) - Yu, Bo; Sun, Ying-Bo; Huang, Li-Li; Xu, Ye-Chun; Zhao, Chao-Yi; Liu, Xiao-Fei
Abstract: Camellia chuongtsoensis is an evergreen shrub with a single-petaled flower and golden yellow color. The complete chloroplast genome of C. chuongtsoensis was sequenced and analyzed in this study by Illumina sequencing. The chloroplast genome is 156, 504 bp in length with a quadripartite structure containing a large single copy (LSC) region of 86, 215 bp, a small single copy (SSC) region of 18, 253 bp, and a pair of inverted repeat regions of 26, 018 bp (IRa and IRb). The chloroplast genome of C. chuongtsoensis encodes 135 genes, comprising 87 protein-coding genes, 37 tRNA genes, 8 rRNA genes, and 3 pseudogenes.